Zathura - Favreau, Jon.; Bobo, Jonah; Hutcherson, Josh.; Shepard, Dax.; Stewart, Kristen, 1990-; Robbins, Tim, 1958-; Van Allsburg, Chris; Sony Pictures Home Entertainment (Firm) ([Culver City, Calif.] : Sony Pictures Home Entertainment, 2006)
Danny twists the key of an old science fiction game. The game unleashes a localized meteor shower and wrenches Danny's house into orbit around a distant ringed planet. Besides Danny, his brother Walter and sister Lisa have to go along. Soon a defective robot, a rangy astronaut, and an alien spaceship enter the picture. The only way the kids can return their house to its proper space-time coordinates is to finish the game, but before they can finish, the game board falls into the hands of some rather nasty, carnivorous lizards.
Widescreen (1.85:1) presentation.
Based on the book by Chris Van Allsburg.
Originally released as a motion picture in 2005.
Special features: Jon Favreau and Peter Billingsley commentary; "The making of 'Zathura' featurette; visual effects documentary; the cast of 'Zathura'; Zorgons, Robots and 'Frozen Lisa'; making the game; miniatures and the world of 'Zathura'; the world of Chris van Allsburg.
Director of photography, Guillermo Navarro ; art directors, David F. Klassen, Richard F. Mays ; editor, Dan Lebental ; music, John Debney ; costume designer, Laura Jean Shannon ; production designer, J. Michael Riva ; visual effects supervisors, Joe Bauer, Peter G. Travers.
Jonah Bobo, Josh Hutcherson, Dax Shepard, Kristen Stewart, Tim Robbins, John Alexander.
Keywords: Board games -- Drama; Orbital transfer (Space flight) -- Drama; Brothers and sisters -- United States -- Drama; Science fiction films; Feature films